Investigating visual engagement of Generation Z with presidential campaign infographics through Eye-Tracking technology - Indra, Evta; Hizkia, Hidayati; Ginting, Hardiansah; Stanley, Calvin; Harnita, Pratiwi Cristin; Akbari, Deni Adha; Edison, Rizki Edmi (Journal of Natural Sciences and Mathematics Research, 2024)
This study was designed to investigate the visual engagement of Generation Z with Indonesian presidential election campaign infographics utilizing eye-tracking technology. Notably, Generation Z forms a significant segment of first-time voters in the 2024 General Election and plays an integral role in political decision-making processes. Despite their pivotal role, a marked disengagement with political activities among this demographic presents significant challenges. Prior research has demonstrated that visual attention is modulated by experiential factors and personal biases. Consequently, this investigation seeks to elucidate the impact of infographics on the visual attention of participants with pre-established preferences for presidential candidates. Employing eye-tracking technology facilitated an objective assessment of the participants' subconscious reactions to the infographics. This study analyzed the distribution of visual attention across six defined Regions of Interest (ROI) among 60 participants. The findings reveal that 50% of the participants directed their gaze predominantly at the names of the candidate pairs, 27% at the image of the presidential candidate, 15% at quotes, 5% at the image of the vice-presidential candidate, 2% at the candidate number, and 1% at the vision statement. Additionally, it was observed that 55% of the participants consistently fixated on the infographics that corresponded to their preferred candidate pair from the onset to the conclusion of the recording, while 45% demonstrated variability in their viewing patterns. These insights afford valuable implications for political strategists aiming to forge more effective communication strategies with Generation Z, thereby enhancing their engagement in the political discourse, particularly in the context of general elections.